A Seven-Year Audit of Intensive Care Unit Admissions and Outcome in a Tertiary Care Hospital in Nepal - Sharma, Sachit; Shrestha, Gentle Sunder; Shrestha, Pramesh Sundar; Paneru, Hem Raj; Pathak, Sunil; Rijal, Divas; Acharya, Subhash Prasad (Journal of Institute of Medicine Nepal, 2025)
Introduction An audit is used to assess if a particular aspect of health care is in accordance with the standard practice and aims to achieve improvement in quality for the benefit of the patient. The current study is a retrospective descriptive observational audit which intends to study the patient profile and outcome of patients admitted to a level III ICU of a tertiary care hospital in Nepal over a duration of seven years. Methods A retrospective descriptive observational audit was conducted in the Tribhuvan University Teaching Hospital (TUTH) ICU from 1st Baisakh, 2074 to 31st Chaitra, 2080. Data on patient profile and outcome were recorded and statistical analysis was performed. Results A total of 6,233 patients were admitted, with 53.9% male patients over a duration of 7 years in TUTH ICU. Medical admissions accounted for 51.67% and surgical admissions 48.33%. Overall, the maximum number of cases were admitted under neurosurgical speciality. Of all patients, 64.7% improved and were shifted out of ICU while mortality was 27.4%. An average sequential organ failure assessment (SOFA) score was 6.7 during the study period. Conclusion The major finding of the study was a progressive decline in average SOFA score, average length of ICU stay and average length of Mechanical Ventilation over the last 3 years. The highest number of admission was in neurosurgery and respiratory medicine over the duration of seven years.